PLANETARY CAATINGIZATION: THE BRAZILIAN SEMI-ARID AS A BLUEPRINT FOR ADAPTATION IN THE ANTHROPOCENE - Roberto Ramos, Paulo; Almeida Ferreira, Rodrigo; Dourado Carvalho, Luzineide; de Almeida Araújo, Cleyton; Cordeiro Pereira, Sidclay; Frensch, Gustavo; Silva Carvalho, Rubens; Lemos Cavalcante de Carvalho Santiago, Beatriz; de Deus Cysneiros Cavalcanti, Airton; Mara Marinho da Silva, Lícia; Gomes de Lima, Carlos; Santana de Jesus, Mariana; et al. (Revista Gênero e Interdisciplinaridade, 2026)
The global expansion of drylands represents one of the most pressing challenges of the Anthropocene, challenging development models historically grounded in climatic stability and resource abundance. Within this context, the central problem concerns how systems adapted to scarcity can inform global adaptation strategies. This study aims to analyze how the biological, technological, and social model of the Brazilian Caatinga can serve as a paradigm for the emerging climatic “new normal.” Methodologically, an integrative literature review was conducted using an interdisciplinary approach, drawing on international scientific databases and environmental data through a systematic selection and thematic analysis process. The results reveal a convergence of global climate toward semi-arid conditions, the high adaptive complexity of Caatinga biodiversity, and the effectiveness of social technologies based on coexistence with environmental variability. The discussion highlights the need to move beyond the paradigm of abundance and adopt resilience-centered frameworks, culminating in the proposal of the “Epistemology of the Thorn” as a novel interpretive model. It is concluded that the Caatinga constitutes an anticipatory system of future planetary conditions and should be recognized as a strategic reference for global adaptation policies and practices.